Relationship Between Myocardial Perfusion Imaging Abnormalities on Positron Emission Tomography and Anginal Symptoms, Functional Status, and Quality of Life. (February 2022) - Patel, Krishna K.; Patel, Femina S.; Bateman, Timothy M.; Kennedy, Kevin F.; Peri-Okonny, Poghni A.; McGhie, A. Iain; Sperry, Brett W.; Shaw, Leslee; Di Carli, Marcelo; Thompson, Randall C.; Saeed, Ibrahim M.; Jones, Philip G.; et al.
Abstract : Background: Myocardial perfusion imaging (MPI) identifies abnormalities that occur early in the ischemic cascade leading to angina. Our aim was to study the association between ischemic measures on positron emission tomography MPI and patients' health status; their symptoms, function, and quality of life. Methods: Health status was collected using the Seattle Angina Questionnaire (SAQ-7, 0–100, higher=better) and Rose Dyspnea Score (RDS) on 1515 outpatients with known or suspected coronary artery disease presenting for clinically indicated pharmacological 82 Rb positron emission tomography MPI from July 2018 to July 2019. Adjusted multivariable ordinal regression models were used to assess the association between MPI findings of ischemia and the SAQ physical limitation, angina frequency, quality of life, summary score, and the RDS. Results: The mean SAQ and RDS scores of the cohort (mean age 71.7 years, 55% male, 37.6% prior myocardial infarction or revascularization) were 73.8±28.6 (physical limitation), 87.4±21.7 (angina frequency), 79.0±26.1 (quality of life), 81.3±19.0 (summary score), and 2±2 (RDS). No perfusion, flow or function abnormalities were significantly associated with SAQ angina frequency scores. Low left ventricular ejection fraction reserve (⩽0%), low global and regional myocardial blood flow reserve (<2) were independently associated with worse SAQ Physical Limitation score, SAQ summary score, and RDS (30% to 57% greater odds; all P ⩽0.01), but reversible perfusion defects were not. Conclusions: Impaired augmentation of left ventricular ejection fraction and myocardial blood flow with stress is associated with significant angina-associated functional limitation, health status, and dyspnea in patients who underwent positron emission tomography MPI, but not the frequency of their angina. Future studies should evaluate whether therapies that improve stress-induced abnormalities in systolic function and myocardial flow may improve patients' health status. Abstract : Supplemental Digital Content is available in the text.